VMware Cloud Foundry - Isaacs, Andrew M.; Kanakamedala, Sam; Reed, Lisa (London : SAGE Publications Ltd, 2017)
In April 2011, VMware announced the worlds first open Platform-as-a-Service (PaaS) offering, Cloud Foundry. The service provided a platform for building, deploying, and running cloud applications. It offered developers a choice of developer frameworks, infrastructure services, and clouds to which to deploy applications. Cloud Foundry was intended to allow software developers to focus on applications development rather than infrastructure. Jerry Chen, VMwares Vice President of Cloud and Application Services, was responsible for identifying the appropriate business model for Cloud Foundry. He knew that success for the service would be measured both in terms of establishing a vibrant ecosystem and building a successful business on the platform itself. He and his team needed to find the right balance between VMwares own in-house Software-as-a-service (SaaS) offerings and potential partners or acquisitions.
Originally published in Isaacs, A. M., Kanakamedala, S., & Reed, L. (2012). VMware Cloud Foundry. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; VMware Cloud Foundry; Business planning; Software engineering